Neonatal infections in Asia. Issue 2 (19th September 2008) - Tiskumara, R; Fakharee, S H; Liu, C Q; Nuntnarumit, P; Lui, K M; Hammoud, M; Lee, J K F; Chow, C B; Shenoi, A; Halliday, R; Isaacs, D
Abstract : Objective: To study the epidemiology (including incidence, antibiotic sensitivity and mortality) of neonatal unit infections in countries in Asia. Methods: One year prospective study of neonatal infections in eight neonatal units in Asia. Results: There were 453 episodes of sepsis affecting 394 babies. Mortality from neonatal sepsis was 10.4%, with an incidence of 0.69 deaths/1000 live births. Group B streptococcus was the most common early-onset organism causing 38% of episodes of early-onset (<48 h old) sepsis, with a rate of 0.51 episodes per 1000 live births and a mortality of 22%. Gram-negative bacillary early-onset sepsis occurred at a rate of 0.15 episodes per 1000 live births with a mortality of 12%. There were 406 episodes of late-onset sepsis. The incidence was high at 11.6 per 1000 live births, and mortality was 8.9%. Coagulase-negative staphylococcus caused 34.1% of episodes, whereas Staphlococcus aureus caused only 5.4%. Gram-negative bacilli caused 189 episodes (46.6%). Only 44% of Gram-negative bacilli were sensitive to both gentamicin and a third-generation cephalosporin, whereas 30% were resistant to both antibiotics. Meningitis occurred in 17.2% of episodes of late sepsis, with a mortality of 20%. Conclusions: The incidence of late-onset sepsis was higher in Asia than in resource-rich countries, but the organisms isolated and mortality were similar. Over half of all Gram-negative bacilli were antibiotic resistant.